Composite hydrogel as well as preparation method and application thereof

By regulating the ratio and preparation process of PVA, COS and DA, PVA/COS/DA composite hydrogels with high adhesion strength and high tensile properties are synthesized, which solves the problems of poor adhesion and low tensile strength of hydrogels in the prior art.

CN119798708APending Publication Date: 2025-04-11GUANGDONG PHARMA UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411779334.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing PVA/COS/DA composite hydrogels have poor adhesion and low tensile strength, which is difficult to meet the high adhesion and high flexibility requirements in tissue engineering.

Method used

By regulating the ratio and preparation process of PVA, COS and DA, PVA/COS/DA composite hydrogel is synthesized by one-pot cross-linking method, and the hydrogel network structure is regulated to improve adhesion strength and tensile performance.

Benefits of technology

The high adhesion strength and high tensile properties of PVA/COS/DA composite hydrogel are achieved, which enhances its application potential in tissue engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798708A_ABST
    Figure CN119798708A_ABST
Patent Text Reader

Abstract

The invention provides composite hydrogel as well as a preparation method and application thereof, and belongs to the technical field of hydrogel. The preparation method comprises the following steps: mixing a PVA (Polyvinyl Alcohol) aqueous solution, chitosan oligosaccharide and dopamine hydrochloride, dropwise adding a glutaraldehyde aqueous solution, uniformly mixing, and heating to obtain composite hydrogel; wherein the molecular weight of the chitosan oligosaccharide is less than 1000. The PVA / COS / DA composite hydrogel prepared by the preparation method disclosed by the invention has excellent mechanical strength and adhesion strength at the same time by adjusting the dosage ratio of the chitosan oligosaccharide, the glutaraldehyde and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogels and relates to a composite hydrogel and a preparation method and application thereof. Background Art

[0002] The skin is the largest organ covering the whole body and is also one of the organs most vulnerable to external damage. Skin repair materials have always been an important research object for the development of new biomaterials. At present, many types of new wound dressing materials have been developed, such as hydrogel matrices, porous scaffolds, woven dressings, injectable beads, nanofibers, etc. Among them, hydrogels have a hydrophilic three-dimensional cross-linked polymer network that can keep wounds moist and are believed to be widely used to repair the structure and function of damaged skin. However, the existing commercially available hydrogel materials still have problems such as complex preparation process, poor adhesion, and low tensile strength.

[0003] Polyvinyl alcohol (PVA) is a water-soluble polymer material made by polymerizing and alcoholyzing vinyl acetate. It contains a large number of hydrophilic active groups in its structure, has good swelling, film-forming and mechanical properties, has no toxicity or irritation to the body and tissue cells, can maintain the moist condition near the wound, and is conducive to the growth and repair of epithelial cells. Compared with ordinary dressings, the wound healing time is shorter and it can be slowly degraded in the body. The preparation method is simple and has good repeatability. It is one of the main raw materials for synthetic hydrogel dressings. PVA hydrogel is a semi-crystalline gel material made of water-soluble PVA by physical or chemical cross-linking treatment. It is easy to synthesize and has excellent water solubility, self-healing, biocompatibility and natural degradability in soil. In the field of biomedicine, it is often used as a drug sustained-release carrier, a substitute for repairing or reproducing cartilage tissue, and artificial fiber muscle. However, hydrogels synthesized from single PVA are usually inactive, have poor elasticity and mechanical properties, poor adhesion to biological tissues, and have defects in tissue engineering, which greatly limits its promotion and application.

[0004] Chitosan oligosaccharide (COS), also known as oligochitosan, is formed by the depolymerization of chitosan. Chitosan is the product of chitin deacetylation. It is a natural high molecular polymer with a wide range of sources and many unique properties such as degradability, biocompatibility, non-toxicity, hemostasis, and antibacterial properties. It has low cost and excellent performance, so it is widely used in cosmetics, antibacterial agents, and medical materials. Although chitin and chitosan have multiple biological activities, their insolubility in water limits their application in many industrial fields.

[0005] Dopamine (DA) is a tyrosine derivative and an analog of mussel protein. It has a similar molecular structure, the catechol group, and has excellent cell affinity and adhesion properties, especially adhesion in a wet environment. The dynamic bonds based on catechol are easily broken, which effectively dissipates energy, allowing the design of hydrogels with excellent toughness and stretchability. Hydrogels containing catechol groups have high tissue adhesion strength under wet conditions and can effectively protect cells from oxidative stress damage and inhibit inflammatory responses. Although the main adhesion mechanism has not yet been clarified, studies have found that the catechol structure of dopamine is easily oxidized to a quinone or semiquinone structure, which can be connected to the quinone group with amine-containing molecules through Schiff base or Michael addition reactions. Therefore, the introduction of dopamine is expected to endow hydrogels with antioxidant, adhesive, self-healing and high toughness.

[0006] Chinese invention patent CN117050336A provides a polyvinyl alcohol / carboxymethyl chitosan / PDA@EGCG NPs hydrogel and its preparation method and application. First, EGCG-modified polydopamine nanoparticles PDA@EGCGNPs are synthesized, and then PDA@EGCGNPs are dispersed in a polyvinyl alcohol / carboxymethyl chitosan blend solution and cross-linked to obtain a polyvinyl alcohol / carboxymethyl chitosan / PDA@EGCGNPs hydrogel. Among them, polyvinyl alcohol and carboxymethyl chitosan form a double network during the hydrogel formation process due to the intermolecular hydrogen bond interaction. The addition of EGCG@NPs nanoparticles enhances the mechanical properties and antioxidant properties of the composite hydrogel, and gives the hydrogel excellent photothermal properties. However, the hydrogel prepared by this technology has problems such as poor adhesion and low tensile strength.

[0007] In summary, the prior art fails to provide a PVA / COS / DA composite hydrogel and preparation process with good tensile strength and good adhesion performance. Summary of the invention

[0008] In view of this, in view of the above problems existing in the prior art, the object of the present invention is to provide a composite hydrogel and a preparation method and application thereof.

[0009] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing a composite hydrogel, comprising the following steps:

[0010] PVA aqueous solution, chitosan oligosaccharide and dopamine hydrochloride are mixed, glutaraldehyde aqueous solution is added dropwise, mixed and heated to obtain a composite hydrogel; wherein the molecular weight of the chitosan oligosaccharide is less than 1000.

[0011] Preferably, the weight concentration of PVA in the PVA aqueous solution is 5%-15%, more preferably 10%.

[0012] Preferably, the weight ratio of PVA, chitosan oligosaccharide and dopamine hydrochloride in the PVA aqueous solution is 5:2-10:1, more preferably 5:6:1.

[0013] Preferably, the mass concentration of glutaraldehyde in the glutaraldehyde aqueous solution is 45%-55%, more preferably 50%.

[0014] Preferably, the weight ratio of the chitosan oligosaccharide to the glutaraldehyde aqueous solution is 0.5-2:1.

[0015] Preferably, the heating temperature is 60-70°C, more preferably 65°C.

[0016] Preferably, the heating time is 2 min-6 h.

[0017] More preferably, the heating is specifically: placing in an oven, heating at 65° C. until solidified into gel. The solidification time is 2 min-6 h.

[0018] On the other hand, the present invention provides a composite hydrogel prepared by the above preparation method.

[0019] In another aspect, the present invention provides application of the above preparation method in producing composite hydrogel.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a method for preparing a PVA / COS / DA composite hydrogel, wherein the PVA / COS / DA composite hydrogel is synthesized by a one-pot cross-linking method. The hydrogel network structure is regulated by regulating the raw material ratio and the preparation process, thereby simultaneously maintaining the flexibility and adhesion of the hydrogel, and improving its adhesion strength and tensile properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the infrared spectra of the composite hydrogel, PVA / COS, PVA and COS prepared in Example 1.

[0023] Figure 2 These are scanning electron microscope (SEM) photos of the composite hydrogel prepared in Example 1 at different magnifications, wherein the photo on the right is a magnified photo of the framed area in the photo on the left.

[0024] Figure 3 These are photos of the composite hydrogels prepared by the methods provided in Examples 1 to 5 before and after heating and curing.

[0025] Figure 4 These are photos of the composite hydrogels prepared by the preparation methods provided in Example 1, Example 6, Example 7 and Comparative Example 1 before and after heating and curing.

[0026] Figure 5 It is a schematic diagram of the composite hydrogel adhesion ability test.

[0027] Figure 6 This is a schematic diagram of the composite hydrogel stretching ability test. DETAILED DESCRIPTION

[0028] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.

[0029] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.

[0030] In the following examples, some raw material information is shown in Table 1:

[0031] Table 1

[0032]

[0033] In the following examples, the instrument information used is shown in Table 2:

[0034] Table 2

[0035]

[0036]

[0037] Example 1

[0038] Preparation of PVA / COS / DA composite hydrogel. The steps are as follows:

[0039] Dissolve 0.5g of PVA in an appropriate amount of water to prepare a 10% PVA aqueous solution. Stir and mix the PVA aqueous solution, 0.6g of chitosan oligosaccharide, and 100mg of dopamine hydrochloride. Then add 0.6g of a 50% glutaraldehyde aqueous solution. The amount of chitosan oligosaccharide and 50% glutaraldehyde aqueous solution is 1:1. Stir evenly. The stirred liquid is divided into two parts, one is placed in a transparent glass bottle with a lid for the determination of the curing time, and the other is placed in a mold (polytetrafluoroethylene mold, size 5cm×2cm×3mm) for adhesion and tensile properties testing. Heat in an oven at 65°C to obtain a PVA / COS / DA composite hydrogel.

[0040] Example 2

[0041] Compared with Example 1, the difference is that the amount of chitosan oligosaccharide is changed to 0.4 g, the amount of 50% glutaraldehyde aqueous solution is changed to 0.4 g, and the rest is the same.

[0042] Example 3

[0043] Compared with Example 1, the difference is that the amount of chitosan oligosaccharide is changed to 0.8 g, the amount of 50% glutaraldehyde aqueous solution is changed to 0.8 g, and the rest is the same.

[0044] Example 4

[0045] Compared with Example 1, the difference is that the amount of chitosan oligosaccharide is changed to 0.2 g, the amount of 50% glutaraldehyde aqueous solution is changed to 0.2 g, and the rest is the same.

[0046] Example 5

[0047] Compared with Example 1, the difference is that the amount of chitosan oligosaccharide is changed to 1.0 g, the amount of 50% glutaraldehyde aqueous solution is changed to 1.0 g, and the rest is the same.

[0048] Example 6

[0049] Compared with Example 1, the difference is that the amount of the 50% glutaraldehyde aqueous solution is changed to 0.4g, and the rest is the same. The amount of chitosan oligosaccharide and the 50% glutaraldehyde aqueous solution is 1.5:1.

[0050] Example 7

[0051] Compared with Example 1, the difference is that the amount of the 50% glutaraldehyde aqueous solution is changed to 0.3g, and the rest is the same. The amount of chitosan oligosaccharide and the 50% glutaraldehyde aqueous solution is 2:1.

[0052] Comparative Example 1

[0053] Compared with Example 1, the difference is that the amount of the 50% glutaraldehyde aqueous solution is changed to 0.24g, and the rest is the same. The amount of chitosan oligosaccharide and the 50% glutaraldehyde aqueous solution is 2.5:1.

[0054] Example 8

[0055] Compared with Example 1, the difference is that the amount of the 50% glutaraldehyde aqueous solution is changed to 1.2g, and the rest is the same. The amount of chitosan oligosaccharide and the 50% glutaraldehyde aqueous solution is 0.5:1.

[0056] Comparative Example 2

[0057] The hydrogel is prepared by the preparation method provided in Example 1 of prior art CN117050336A.

[0058] Effect evaluation

[0059] 1. Material structure characterization experiment

[0060] 1.1 Infrared Spectroscopy

[0061] Appropriate amounts of PVA, COS, PVA / COS, and the PVA / COS / DA hydrogel freeze-dried samples prepared in Example 1 were placed in a sample cell and tested using a Fourier transform infrared spectrometer.

[0062] Wherein, the preparation method of PVA / COS is as follows:

[0063] 0.5g PVA is made into a 10% aqueous solution, 0.6g chitosan oligosaccharide is added, the mixture is stirred evenly, and freeze-dried to obtain the product.

[0064] The parameters are: 64 scans, 4 cm resolution -1 , wave number range 400-4000cm -1 The results are as follows Figure 1 shown. Figure 1 Medium, 1037cm -1 The absorption peak of chitosan oligosaccharide CO stretching vibration is 1713 cm -1 The carbonyl peak near 1635cm is caused by the incomplete alcoholysis of polyvinyl alcohol. In the infrared spectra of PVA / COS and PVA / COS / DA hydrogels, compared with COS, the peak at 1635cm -1 A narrow and sharp absorption peak appeared at 1528 cm, which is the characteristic absorption peak of C=N in the Schiff base structure. Compared with the infrared spectrum of PVA / COS hydrogel, the hydrogel containing DA has a -1 A new absorption peak appears at 3300 cm, which is the characteristic absorption peak of aromatic C=C double bond, and further illustrates the existence of catechol structure in the composite hydrogel. -1 The absorption peaks on the left and right become broader and move toward the lower wavenumber direction, indicating that PVA, DA, and COS interact with each other and form hydrogen bonds with each other. These characteristics all indicate the successful preparation of PVA / COS / DA composite hydrogel.

[0065] 1.2 Scanning electron microscopy analysis

[0066] The surface morphology of the freeze-dried PVA / COS / DA hydrogel prepared in Example 1 was observed using a scanning electron microscope (SEM) at a voltage of 15 kV. Figure 2 shown. Figure 2It can be seen that there are uneven protrusions on the surface of the hydrogel, which may have two causes. One is that dopamine self-polymerizes in the solution to form tiny particles, and these particles are deposited on the surface of the gel and form protrusions; the other is that dopamine can interact with the hydroxyl or amine groups in PVA and chitosan oligosaccharides through hydrogen bonds. This interaction may affect the formation process of the gel, resulting in the unevenness of the gel network structure, and also causing dopamine to form an uneven distribution on the surface of the material, resulting in surface protrusions. The fact that these protruding parts are in direct contact with another surface is one of the reasons for the improved adhesion of the prepared hydrogel.

[0067] 2. Determination of gelation time

[0068] Method for measuring gelation time: The gelation time of the hydrogel is measured by the tube inversion method. Place the sample bottle containing the mixed solution in a 65°C oven and start timing. Invert the bottle every once in a while. If the gel does not flow, it indicates that the gelation is stable. Record the gelation time.

[0069] The gelation time and gelation conditions of the composite hydrogels prepared in various embodiments and comparative examples are shown in Table 3:

[0070] Table 3

[0071]

[0072]

[0073] The photo of the gelling effect is as follows Figure 3 , 4 shown.

[0074] It can be seen that in Example 4, the amount of chitosan oligosaccharide used was too little, the gelation time was long, and the gelation was not complete. This may be because the amino group in dopamine also reacted with glutaraldehyde to form a Schiff base, resulting in a reduction in glutaraldehyde reacting with chitosan oligosaccharide, insufficient crosslinking and prolonged reaction time. However, as the concentration of chitosan oligosaccharide continued to increase, the number of crosslinking points in the hydrogel increased, the gelation rate accelerated, and the hydrogel gelation time became shorter and shorter.

[0075] In Example 1, Example 6-Example 8, as the amount of glutaraldehyde is reduced, the gelation time is gradually prolonged. This indicates that the rate and degree of the cross-linking reaction are reduced, and the network structure is formed more slowly. When the amount of glutaraldehyde is too low, the rate and degree of the cross-linking reaction are too low, and a stable three-dimensional network structure cannot be formed, and a gel cannot be formed.

[0076] 3. Adhesion performance test

[0077] Treated fresh pig skin was used instead of human skin for testing.

[0078] The specific steps are as follows: First, soak fresh pig skin in 9% sodium chloride aqueous solution for 3 hours, and scrape off the fat layer on the surface of the pig skin. Second, cut the pig skin into 20mm×50mm rectangles with a blade, and wipe off the excess water on the surface. Then, place the sheet hydrogel of the same specifications prepared on the mold on the surface of the pig skin, and then cover it with a layer of pig skin of the same size, as shown in the schematic diagram. Figure 5 .

[0079] A digital tensile test was performed to apply a certain pressure to the adhesion point, and the instrument was pulled at a fixed rate to record the maximum tensile force during the separation of the two pieces of pigskin, which was recorded as N. max According to the formula: Pa = N max ÷S to calculate the adhesion strength of hydrogels with different concentrations. Where Pa is the adhesion strength and S is the effective area of ​​hydrogel adhering to pig skin.

[0080] The skin adhesion test results of the composite hydrogels prepared in various embodiments and comparative examples are shown in Table 4:

[0081] Table 4

[0082] Group Adhesion strength (kPa) Example 1 0.73 Example 2 0.98 Example 3 0.64 Example 4 5.00 Example 5 1.73 Example 6 2.18 Example 7 2.68 Comparative Example 1 Uncured, cannot be measured Example 8 1.02 Comparative Example 2 0.68

[0083] In the hydrogel, PVA, COS and DA can be combined with each other through various interaction forces such as hydrogen bonds and van der Waals forces. As the concentration of chitosan oligosaccharides increases, the ratio between chitosan oligosaccharides and polyvinyl alcohol and dopamine also changes, and the interaction force between the three will also change. Specifically, the ratio of chitosan oligosaccharides, dopamine hydrochloride and polyvinyl alcohol in the hydrogel provided in Example 4 helps to enhance the network structure, and therefore has a higher adhesion strength. Within the range of Example 1-Example 4, with the increase in the proportion of chitosan oligosaccharides, the interaction between chitosan oligosaccharide molecules may become stronger, and the interaction between chitosan oligosaccharides and PVA and DA molecules is weakened, causing the network structure to become looser, thereby possibly reducing the adhesion strength. Compared with Example 3, the proportion of chitosan oligosaccharides in Example 5 increases, and the adhesion strength of the hydrogel is improved instead. The reason may be that the overall network structure is tighter.

[0084] 4. Tensile performance test

[0085] A rectangular sample (5 cm long, 2 cm wide, 3 mm thick) made of hydrogel was placed on a universal tensile machine for tensile length testing at a tensile speed of 5 mm / min until the sample broke (e.g. Figure 6 As shown). The tensile strength and elongation at break are calculated based on the relationship between force and displacement. The tensile strength is the ratio of the force that the material bears during the stretching process to the cross-sectional area of ​​the material, and the unit is kPa; the elongation at break is the percentage of the elongation of the material when it breaks during the stretching process to the original length.

[0086] The tensile properties test results of the composite hydrogels prepared in various embodiments and comparative examples are shown in Table 5:

[0087] Table 5

[0088]

[0089] When the hydrogel is stretched, if it contains a large number of PVA-COS-DA cross-linked structures, these cross-linked structures can break bonds after tensile stress is generated, consume energy and relieve stress concentration. Such a mechanism can prevent the formation of macroscopic breaking points, thereby giving the hydrogel a higher elongation at break. When the concentration of chitosan oligosaccharides is low, PVA, COS, and DA form a stable cross-linked structure with good tensile properties. However, with the increase of chitosan oligosaccharide concentration, the tensile strength and elongation at break of the hydrogel dropped significantly, indicating that the increase of chitosan oligosaccharides significantly enhanced the rigidity and brittleness of the hydrogel system. This is because the increase in chitosan oligosaccharide concentration leads to an increase in the number of cross-linking points, increases the cross-linking density, and forms a tighter network structure. Such a network structure cannot release energy when stretched, and microscopic defects are more likely to rapidly develop into macroscopic defects due to stress concentration, ultimately leading to gel fracture.

[0090] The mechanical strength of hydrogels is almost entirely due to the crosslinking of the gel. The greater the amount of glutaraldehyde used as a crosslinking agent, the greater the crosslinking density. As the degree of crosslinking of the gel increases, the mobility of the gel network molecular chains decreases, and the rigidity of the gel also decreases. Therefore, when the content of the crosslinking agent glutaraldehyde decreases, the crosslinking density decreases, the mechanical strength is reduced, the deformation range is expanded, and the elongation at break is increased. However, low crosslinking density may cause the internal interaction force of the hydrogel to weaken, and it will be unable to resist external forces when stretched, and the tensile strength will be reduced.

[0091] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a composite hydrogel, characterized in that: The following steps are involved: The PVA aqueous solution, chitosan oligosaccharide and dopamine hydrochloride are mixed, and the glutaraldehyde aqueous solution is added dropwise, mixed and heated to obtain a composite hydrogel; Wherein, the molecular weight of the chitosan oligosaccharide is less than 1000.

2. The preparation method according to claim 1, characterized in that: The weight concentration of PVA in the PVA aqueous solution is 5%-15%.

3. The preparation method according to claim 1, characterized in that: The weight ratio of PVA, chitosan oligosaccharide and dopamine hydrochloride in the PVA aqueous solution is 5:2-10:

1.

4. The preparation method according to claim 1, characterized in that: The mass concentration of glutaraldehyde in the glutaraldehyde aqueous solution is 45%-55%.

5. The preparation method according to claim 1, characterized in that: The weight ratio of the chitosan oligosaccharide to the glutaraldehyde aqueous solution is 0.5-2:

1.

6. The preparation method according to claim 1, characterized in that: The heating temperature is 60-70°C.

7. The preparation method according to claim 1, characterized in that: The heating time is 2 min-6 h.

8. The preparation method according to claim 6 or claim 7, characterized in that: The heating specifically includes placing the mixture in an oven and heating it at 65° C. until the mixture is cured into a glue.

9. The composite hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the preparation method according to any one of claims 1 to 8 in producing composite hydrogels.

Citation Information

Patent Citations

  • Polyvinyl alcohol / carboxymethyl chitosan / PDA coated EGCG NPs hydrogel as well as preparation method and application thereof

    CN117050336A